DEVELOPMENT OF NEW SAFE FLUX FOR ALUMINIUM AND ITS ALLOYS - N. V. Sletova; V. A. Chajkin; S. P. Zadrutskij; V. A. Rozum (Литьë и металлургия)
It is shown that application of the new combined flux metal will allow to improve ecological conditions in casthouse, with use of waste of the used agglutinant sand will give the possibility to carry out the reclaiming of the soils.